Monitoring safety in a phase III real‐world effectiveness trial: use of novel methodology in the Salford Lung Study. Issue 3 (1st November 2016) - Collier, Sue; Harvey, Catherine; Brewster, Jill; Bakerly, Nawar Diar; Elkhenini, Hanaa F.; Stanciu, Roxana; Williams, Claire; Brereton, Jacqui; New, John P.; McCrae, John; McCorkindale, Sheila; Leather, David
Abstract: Background: The Salford Lung Study (SLS) programme, encompassing two phase III pragmatic randomised controlled trials, was designed to generate evidence on the effectiveness of a once‐daily treatment for asthma and chronic obstructive pulmonary disease in routine primary care using electronic health records. Objective: The objective of this study was to describe and discuss the safety monitoring methodology and the challenges associated with ensuring patient safety in the SLS. Refinements to safety monitoring processes and infrastructure are also discussed. The study results are outside the remit of this paper. The results of the COPD study were published recently and a more in‐depth exploration of the safety results will be the subject of future publications. Achievements: The SLS used a linked database system to capture relevant data from primary care practices in Salford and South Manchester, two university hospitals and other national databases. Patient data were collated and analysed to create daily summaries that were used to alert a specialist safety team to potential safety events. Clinical research teams at participating general practitioner sites and pharmacies also captured safety events during routine consultations. Confidence in the safety monitoring processes over time allowed the methodology to be refined and streamlined without compromising patient safety or the timely collection of data. The information technology infrastructure also allowed additional details of safety information to be collected. Conclusion: Integration of multiple data sources in the SLS may provide more comprehensive safety information than usually collected in standard randomised controlled trials. Application of the principles of safety monitoring methodology from the SLS could facilitate safety monitoring processes for future pragmatic randomised controlled trials and yield important complementary safety and effectiveness data. © 2016 The Authors Pharmacoepidemiology and Drug Safety Published by John Wiley & Sons Ltd.